Pengelolaan Keuangan ditinjau dari Perspektif Self Efficacy dan Financial Knowledge - Novyarni, Nelli; Atikah, Destria Ayu; Harni, Reni; Kartijo, Kartijo (Media Ilmiah Akuntansi, 2024)
Everyone must learn to manage their own finances, including students. Students have the latest attitudes to meet primary and secondary needs. This must be done to avoid failure in managing personal finances with financial knowledge. The aim of this research is to find out how financial knowledge and financial independence impact the personal financial management of Bachelor of Accounting students. The primary and secondary data used in this research are qualitative data which were quantified using a Likert scale. The data collection method is through distributing questionnaires via Google Forms. Classical assumption tests, multiple linear regression analysis, and hypothesis testing were used to analyze the data. Study results from processed data